Exogenous addition of H2 for an in situ biogas upgrading through biological reduction of carbon dioxide into methane - Mulat, Daniel Girma; Polag, Daniela; Greule, Markus; Keppler, Frank (Waste management, 2017)
Biological reduction of CO2 into CH4 by exogenous addition of H2 is a promising technology for upgrading biogas into higher CH4 content. The aim of this work was to study the feasibility of exogenous H2 addition for an in situ biogas upgrading through biological conversion of the biogas CO2 into CH4. Moreover, this study employed systematic study with isotope analysis for providing comprehensive evidence on the underlying pathways of CH4 production and upstream processes. Batch reactors were inoculated with digestate originating from a full-scale biogas plant and fed once with maize leaf substrate. Periodic addition of H2 into the headspace resulted in a completely consumption of CO2 and a concomitant increase in CH4 content up to 89%. The microbial community and isotope analysis shows an enrichment of hydrogenotrophic Methanobacterium and the key role of hydrogenotrophic methanogenesis for biogas upgrading to higher CH4 content. Excess H2 was also supplied to evaluate its effect on overall process performance. The results show that excess H2 addition resulted in accumulation of H2, depletion of CO2 and inhibition of the degradation of acetate and other volatile fatty acids (VFA). A systematic isotope analysis revealed that excess H2 supply led to an increase in dissolved H2 to the level that thermodynamically inhibit the degradation of VFA and stimulate homo-acetogens for production of acetate from CO2 and H2. The inhibition was a temporary effect and acetate degradation resumed when the excess H2 was removed as well as in the presence of stoichiometric amount of H2 and CO2. This inhibition mechanism underlines the importance of carefully regulating the H2 addition rate and gas retention time to the CO2 production rate, H2-uptake rate and growth of hydrogenotrophic methanogens in order to achieve higher CH4 content without the accumulation of acetate and other VFA.
Im Titel ist die Zahl "2" tiefgestellt
Gesehen am 19.02.2018